2021
DOI: 10.3390/jfmk6010027
|View full text |Cite
|
Sign up to set email alerts
|

Kinematic Comparison between Medially Congruent and Posterior-Stabilized Third-Generation TKA Designs

Abstract: Background: This study compares knee kinematics in two groups of patients who have undergone primary total knee arthroplasty (TKA) using two different modern designs: medially congruent (MC) and posterior-stabilized (PS). The aim of the study is to demonstrate only minimal differences between the groups. Methods: Ten TKA patients (4 PS, 6 MC) with successful clinical outcomes were evaluated through 3D knee kinematics analysis performed using a multicamera optoelectronic system and a force platform. Extracted k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…Patients who experienced knee instability showed significantly worse clinical results than those who did not experience knee instability. The medial compartment in medial-pivot TKA has a ball-and-socket shape and is the key to stability 7,8 . The results of this study suggest that if the medial postoperative flexion joint gap increases, knee stability may not be present on the medial side.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who experienced knee instability showed significantly worse clinical results than those who did not experience knee instability. The medial compartment in medial-pivot TKA has a ball-and-socket shape and is the key to stability 7,8 . The results of this study suggest that if the medial postoperative flexion joint gap increases, knee stability may not be present on the medial side.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the medial-pivot TKA might have an advantage in subjective symptoms. Medial-pivot TKA is designed to reproduce the native knee kinematics by providing high medial conformity and ample lateral space, and medial compartment stability is key to knee stability and good postoperative clinical results [6][7][8] . Therefore, in cases in which patients experience subjective knee instability postoperatively, medial-pivot TKA may have a negative effect on PROMs because of its design.…”
mentioning
confidence: 99%
“…Dennis et al showed a reduction in the articular motion and sagittal joint moment following TKA, independently from the level of intra-articular constraint [ 14 ]. Limitation of joint mobility up to a real stiffness represents a well-known strategy adopted by patients with advanced knee OA [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gait Analysis showed to be an accurate and non-invasive tool to study in vivo joints kinetic and kinematic during the range of motion (ROM) [ 12 , 13 , 14 ]. In the TKA world, it has been used to evaluate the in vivo kinematic of the knee during the Load-Response (LR), Mid-Stance (MS) and Swing phases of gait.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 presents some of the initiatives that include the development of force platform projects in the literature. The studies on postural analysis are focused only on the use of force platforms [18][19][20][21][22][23][24][25][26][27] and are much more numerous, differently from the projects and research that show greater emphasis on the development of these platforms. The works analyzed in [5,6,[9][10][11][12][15][16][17] present descriptions that are very superficial and difficult to reproduce, in addition to all making use of load cells for commercial use, significantly increasing the cost of prototypes.…”
Section: Literature Surveymentioning
confidence: 99%